cGAS–STING pathway in ischemia-reperfusion injury: a potential target to improve transplantation outcomes - Chen, Zijian; Liu, Yangqi; Lin, Zeying; Huang, Weizhe (Frontiers in Immunology, 2023)
Transplantation is an important life-saving therapeutic choice for patients with organ or tissue failure once all other treatment options are exhausted. However, most allografts become damaged over an extended period, and post-transplantation survival is limited. Ischemia reperfusion injury (IRI) tends to be associated with a poor prognosis; resultant severe primary graft dysfunction is the main cause of transplant failure. Targeting the cGAS–STING pathway has recently been shown to be an effective approach for improving transplantation outcomes, when activated or inhibited cGAS–STING pathway, IRI can be alleviated by regulating inflammatory response and programmed cell death. Thus, continuing efforts to develop selective agonists and antagonists may bring great hopes to post-transplant patient. In this mini-review, we reviewed the role of the cGAS–STING pathway in transplantation, and summarized the crosstalk between this pathway and inflammatory response and programmed cell death during IRI, aiming to provide novel insights into the development of therapies to improve patient outcome after transplantation.